2001
DOI: 10.1164/ajrccm.163.5.2004197
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Interleukin-5 and Eotaxin Expression in Nasal Polyposis

Abstract: An eosinophilic bronchial inflammation was previously demonstrated in patients with nasal polyposis (NP) and asymptomatic bronchial hyperresponsiveness (BHR) similar to that observed in asthmatic patients with NP, whereas patients with NP without BHR did not. The aim of the study was to investigate the contribution of interleukin 5 (IL-5) and eotaxin to the pathogenesis of BHR associated with NP. Eleven patients with NP without BHR (Group A), 8 patients with NP and asymptomatic BHR (Group B), and 9 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…One possibility is that it reflects the presence of subclinical inflammation within the lower airways. This explanation is supported by data from histopathological studies that demonstrate the presence of bronchial inflammation in nonasthmatic subjects with nasal polyposis [3, 4]. However, the relationship between ENO levels and histologic markers of bronchial inflammation has not been studied in subjects with nasal polyposis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…One possibility is that it reflects the presence of subclinical inflammation within the lower airways. This explanation is supported by data from histopathological studies that demonstrate the presence of bronchial inflammation in nonasthmatic subjects with nasal polyposis [3, 4]. However, the relationship between ENO levels and histologic markers of bronchial inflammation has not been studied in subjects with nasal polyposis.…”
Section: Discussionmentioning
confidence: 93%
“…Nasal polyposis and asthma are related diseases [2], and studies have identified that nasal polyposis may be a risk factor for subsequent development of asthma [37]. Subclinical inflammation in the lower airways has been reported in some nonasthmatic subjects with nasal polyposis [3, 4]. If ENO measurement is a sensitive method of monitoring airway inflammation, it is tempting to speculate that the presence of increased ENO concentrations in subjects with nasal polyposis represents a latent phase of asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, cytokines derived from Th2 cells, which include IL-5 are involved in IgE synthesis and allergic inflammation. Recently, IL-5 has been shown to be involved in allergic inflammation and airway hypersensitiveness [26,38]. In addition, IgE has also been implicated in development of allergic disease and recruitment or accumulation of inflammatory cells such as eosinophils [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Atopic and nonatopic asthma seem to be associated with combined bronchial mucosal expression of CC chemokines (RANTES, eotaxin), together with eosinophilactive cytokines (IL-5, GM-CSF, IL-3) [29,58]. These cytokines may contribute either to the nasal or to the bronchial mucosal accumulation of eosinophils.…”
Section: Role Of CC Chemokines In Chronic Sinusitismentioning
confidence: 99%